Web-based counseling system / Goi Lai Yoong - Goi , Lai Yoong (2002)
Web-based Counseling System is a web-based system develop with the objectives to globally help the people who faced psychological problems reduce or eliminate their difficulties. The system allows authorize user search freely for counseling approach according to their needs. It can be accessible through common web browser and no installation of application in the users' workstation is needed. The system is project proposed by Dr. P. Sellappan. The purpose of Web based Counseling System is to help the government handle the people who needs counseling services with the objectives achieving better the efficiency and effectiveness. Most of the counseling approach will be computerize and also will be integrated with each other through Internet. This Web-based Counseling System will be develop using Active Server Page to create the web program, Microsoft SQL Server 2000 as database server and ITS 5.0 as web server. Visual Basic 6.0 will be used to create the backend administration application for administrator usage to maintain and enhance the web system.